Two new species of Impatiens (Balsaminaceae) from the Western Ghats of Tamil Nadu, India - Raju, Ramasubbu; Surendran, Anjana; Ayyathurai, Chandra Prabha (Phytotaxa, 2020)
Impatiens palniensis and I.tamilnadense are two new species described and illustrated from the Western Ghats of Tamil Nadu, India. Impatiens palniensis collected from Palni hills (Kodaikkanal Wildlife Sanctuary) whereas I. tamilnadense from Megamalai Wildlife Sanctuary.   The detailed description of both taxa along with diagnostic characters between closely allied species, conservation status, pollen morphology and colour photographs are provided.